Comparison of R&D as a competitive advantage between Singapore and various countries. - Koh, Edric Chee Keong. (2008)
This project has been conceived out of a desire to learn what factors affect developing Research and development into a competitive advantage and the extent that benefits can be reaped. It shows that certain initiatives undertaken in Research and development yield benefits for countries in enhancing a countries’ competitive advantage.